WHEN ISLAMIC COSMOPOLITANISM MEET SOCIAL MEDIA TECHNOLOGY: ONLINE/ OFFLINE COMMUNITY, AUTHORITY, AND TRADITION - Supriansyah Supriansyah (TASHWIR, 2022)
Abstract: This article examines the broadcasting of religious activities via social media accounts "Aswajanet" and social dynamics in the community, from November 2019 until August 2020. Aswajanet is the official social media accounts of a young people community in Banjarmasin, which did the broadcasting regularly various online Pengajian (Sermon) or Haul using social networking services. Activities social media Aswajanet does not build the image of Majelis Taklim or Preacher or disseminate information on religious activities only. According to them, broadcasting Haul and Pengajian (Sermon) live via social media does not diminish the meaning contained in this religious ritual. They consider these activities to be part of their efforts to maintain memory and relations with the Ulama, an essential tradition of Islamic traditionalist or Islamic Traditionalist. Using the Ethnographic Digital method, this article collects entire upload status and direct broadcasting religious activity in the interface of social media in the "Aswajanet" account and observing them offline activities. I formally or informally conduct interviews with several of Aswajanet’s activists and some influencer other social media in Banjarmasin. In this article, I ask two primary questions: How is the interaction and articulation of young people in the community Aswajanet with communications technology and the internet? How does social media technology affect authority, collective memory, and Islamic identity in Banjar? As a result, this article has found that majority activity accounts of social media the young Muslim Traditionalist still at rites and religious traditions, such as Pengajian, Haul, and other major religious practices that mediated the computer uploaded online. Besides, through new media, they also carry out discussions, friendships, and support that combine local and online resources, practices, and connections, offering spiritual experiences and new social ties. They emphasize the old identity and tradition, Islam Traditionalistism, among young people rather than replacing it.Keywords: Aswajanet; Islamic Traditionalism; Youth.